Pengaruh Model Scramble Terhadap Hasil Belajar Peserta Didik Pada Tema 9 Benda-Benda Di Sekitar Kita Subtema 1 Di Kelas V SDN 1 Lambheu Aceh Besar - Tesya Ananda Putri; Intan Safiah; Alfiati Syafrina (Jurnal Ilmiah Mahasiswa Pendidikan Guru Sekolah Dasar, 2022)
The review plans to decide the tremendous impact of utilizing the Scramble model on understudy learning results in Theme 9 Objects Around Us Subtheme 1, particularly on single and blended substances. The methodology in this exploration is a quantitative methodology, the kind of examination is True Experimental with a Pretest-Posttest Control Group Design. This examination was directed at the State Elementary School 1 Lambheu Aceh Besar class V Jln Kreung Daroy Utama Perumahan Nasional Lambheu, Darul Imarah District, Aceh Besar District. Testing utilizing soaked examining procedure with an example of all understudies in-class VA and VB with 50 understudies. Information assortment methods involved tests as pretest and posttest, while the information investigation procedure utilized SPSS Statistics 24 and speculation testing with t-test. free. The consequences of speculation testing with free t-test insights got importance esteem (2-followed) of 0.000 0.05. Then the choice standards are Ha acknowledged and H0 dismissed. In this way, it tends to be presumed that there is a huge impact of utilizing the Scramble model on understudy learning results on the topic of 9 items around us, sub-subject 1 in class V SDN 1 Lambheu Aceh Besar.